Defined Plasmodium falciparum antigens in malaria serology - Gabra, M. S. (1986)
The study evaluates three enzyme-linked immunosorbent assays (ELISA) of malaria antigens suitable for use in large-scale epidemiological studies. Results obtained using sera from 567 persons from the Gambia indicated that the micro-ELISA method using parasitized red blood cell extract did not reliably quantitate antimalarial antibodies, especially in young children. In contrast, two micro-ELISA methods that employed purified, defined antigens (a polypeptide of M(r) = 41 000 present in rhoptries, and a 31-1 fusion polypeptide corresponding to a merozoite surface antigen) permitted the precise determination of antimalarial antibodies in both adults and children. Problems and advantages associated with the use of the M(r) = 41 000 and 31-1 antigens for the determination of antimalarial antibodies are discussed.